A Concise Enantiodivergent Synthesis of Equol - Uemura, Takahito; Saito, Yusuke; Sonoda, Motohiro; Tanimori, Shinji (Synlett, 2020)
Equol, a nonsteroidal estrogen produced from the metabolism of the isoflavonoid phytoestrogen daidzein, has been synthesized as both enantioenriched forms based on MacMillan’s α-arylation of carbonyl compound mediated by amino acid derived indazolidinones and copper precatalysts. The natural form of (S)-equol and its enantiomer (R)-equol have been synthesized in 8 steps from 2,4-dimethoxybenzaldehyde with good enantiomeric purity (90% ee and 90% ee, respectively).
Keywords: equol; asymmetric synthesis; isoflavan; α-arylation; MacMillan’s catalyst